Occurrence and distribution of estrogenic chemicals in river waters of Malaysia - Nazifa, Tasnia Hassan; Kristanti, Risky Ayu; Ike, Michihiko; Kuroda, Masashi; Hadibarata, Tony (Korean Society of Environmental Risk Assessment and Health Science, 2020)
Objective: This study investigated the occurrence of eight endocrine-disrupting compounds (EDCs) in river water across fve major regions in Malaysia, which are recognized as emerging micropollutants in the environment.